2012
DOI: 10.1136/flgastro-2012-100118
|View full text |Cite
|
Sign up to set email alerts
|

Scope to improve: a multi-centre audit of 16 064 colonoscopies looking at caecal intubation rates, over a 2-year period

Abstract: Objective Colonoscopy is the 'gold standard' assessment for large bowel mucosal pathology, but a complete examination is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This study’s results demonstrated that the CIR in symptomatic patients is lower than in individuals undergoing colorectal cancer screening. This finding is in line with previous studies 7,12 ; Verma et al. found that the CIRs for screening colonoscopists were higher than for non-screening colonoscopists, and this accounted for the observed difference in CIRs between screening and symptomatic patient groups 12 ; however, we demonstrated that even when looking at just screening colonoscopists, there is still a persistent difference in CIRs between these two groups of patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study’s results demonstrated that the CIR in symptomatic patients is lower than in individuals undergoing colorectal cancer screening. This finding is in line with previous studies 7,12 ; Verma et al. found that the CIRs for screening colonoscopists were higher than for non-screening colonoscopists, and this accounted for the observed difference in CIRs between screening and symptomatic patient groups 12 ; however, we demonstrated that even when looking at just screening colonoscopists, there is still a persistent difference in CIRs between these two groups of patients.…”
Section: Discussionsupporting
confidence: 93%
“…7,12 The aim of this study was to compare colonoscopists' performance, as assessed by CIR in symptomatic patients compared to individuals undergoing colonoscopy for colorectal cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…Of real concern are operators carrying out less than 100 procedures per year; they did not meet the desired CIR quality standard, and performed 4793 colonoscopies 2. We would suggest that this reflects a wider experience in the English health service and needs to be addressed.…”
Section: Discussionmentioning
confidence: 96%
“…The measurement of quality of colonoscopy has been in the vanguard of quality improvement, with two large UK based audits describing key performance standards 1 2. The Joint Advisory Group on Gastrointestinal endoscopy (JAG), an inter-collegiate body responsible for standards, quality and training, has issued guidance for caecal intubation rates (CIR) of 90% or higher on an intention-to-colonoscope basis 3.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent multicentre audit of 16 064 colonoscopies by Verma et al 3 demonstrated the impact that this programme has had. Data over a 2-year period from 2008 to 2009 were collected from six hospitals, 120 endoscopists and 16 064 colonoscopies, demonstrating a marked improvement in the CIR to 90.57%.…”
mentioning
confidence: 99%